Social Support of Community Leaders in the Implementation of the Active Alert Village in Manutapen, Kupang City - Boro, Antonia Ina Maria Palan; Romeo, Petrus; Toy, Sarci Magdalena (Faculty of Public Health, Nusa Cendana University, 2023)
The role of community leaders in implementing the alert village in Manutapen Village should be able to assist and support the running of health programs and the activeness of existing health networks. However, in reality, of the five networks in the Manutapen sub-district, two networks are no longer active, namely the funding network and the family planning network. In addition, in the Manutapen sub-district, there were 2 cases of under-five deaths, 4 cases of malnutrition, and 34 under-fives experiencing stunting. The aim of this research is to describe the form of social support from community leaders in implementing the Active Alert sub-district in Manutapen Sub-District, Alak District, Kupang City in 2021. This research uses a qualitative method with a phenomenological approach. There were 9 research informants using purposive sampling technique. The data analysis technique used is thematic analysis. The results showed that community leaders provide emotional support directly to the community to provide encouragement and direction in each activity, appreciation support by helping overcome health problems and repairing public facilities, instrumental support by coordinating so that all services run well and build public facilities, urban village funding process Alert in the past year has not been running anymore, both fundraising and the budget from the Alert Village itself have not been used due to the busyness of the officers and the Covid 19 pandemic situation. Apart from that, the Alert Village Officers have not yet held a meeting to discuss the Active Alert Village program again. informative support by providing information about the standby village and inviting and mobilizing the community to be involved in implementing the standby village. Community leaders are expected to increase meetings with the community and village alert officers to discuss the village alert program so they can revise programs that are no longer running.